Measuring local job distress - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2021)
In this paper, estimates are presented on short-run effects of demand shocks on a local labor market's employment to population ratio (employment rate). Based on the estimates, commuting zones (CZs) better define a local labor market than counties, because both employment and employment rate effects exhibit large spillovers across counties within a CZ. In addition, the estimates suggest that demand shock effects vary, by an amount that is both statistically and substantively significant, with a CZ's prior overall employment rate.
Keywords: R23; 330; Local labor markets; distressed regions; job creation benefits; local labor demand